Open design and innovation : facilitating creativity in everyone - Cruickshank, Leon. (Gower, 2014)
Open innovation, pro-sumers, disruptive design and brand fanaticism are some of the new approaches to design and innovation that have generated discussion and media coverage in recent years. This book develops the argument for a more nuanced acknowledgement and facilitation of 'non-professional' forms of creativity; drawing on lessons from commercial design practice; theoretical analysis and a wider understanding of innovation. It examines: innovation and design, mass creativity reality and myth, the future of design (practice and profession), through a series of case studies of new approaches to open design practices. The author challenges the notion of the designer as 'fountain-head' of innovation and, equally, the idea of 'user creativity' as a replacement for traditional design and innovation. The book offers a critique of the hype surrounding the emerging phenomena and a framework to help understand the relationship between citizens and designers. --